2022
DOI: 10.1177/19458924221114941
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Sinusitis is a Common Cause of Operative Extra-Sinus Infectious Complications

Abstract: Background Orbital, intracranial, and osseous extra-sinus complications can arise from bacterial or fungal sinusitis. Odontogenic sinusitis (ODS) can cause extra-sinus complications, but its prevalence remains poorly characterized. Objective To determine the frequency of ODS as a cause of operative extra-sinus infectious complications and describe clinical features of all complicated sinusitis cases. Methods A multi-institutional retrospective review was performed on all operative sinusitis-related extra-sinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Additionally, they connected the number of erosions and expansions with disease severity. The development of possible surgical complications and the course of the illness without treatment are both significantly impacted by radiological staging (26)(27)(28) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they connected the number of erosions and expansions with disease severity. The development of possible surgical complications and the course of the illness without treatment are both significantly impacted by radiological staging (26)(27)(28) .…”
Section: Discussionmentioning
confidence: 99%
“…The authors found in their retrospective chart review when unilateral maxillary sinus opacification was found on imaging, 60% of extra-sinus complications were due to odontogenic sinusitis. 7 Simmons et al found an increased incidence of eosinophilic esophagitis in chronic rhinosinusitis patients and encourage clinician awareness for possible concomitant disease, possibly even including dysphagia items in clinical screening. 8 Additionally for asthmatics, Benninger et al report that allergy profiles positive for allergens such as dust mites, some molds, and cat and dog dander was associated with more severe asthma determined by the number of exacerbations and hospitalizations.…”
mentioning
confidence: 96%